A autoridade docente e a sociedade da informa????o: educa????o, crise e liquidez - Soares, Leonardo Humberto (2016)
This research paper aims to identify how the new informational and communicational technologies, the large volume of information produced and the teaching practice across the "Information Society" reinforce and / or puts into question the teachers??? perception of their own authority in the classroom. The study assumed that the sense of "crisis of authority", which is verbalized repeatedly by teachers, might be directly linked to the new emerging social dynamics of technological and informational development seen in the past forty years and it has been increasingly inserted in social and educational context. In this sense, the survey revealed important aspects that might contribute to a better understanding of the educational act itself and on the phenomena that are part of the teacher???s daily routine in the classroom. Taking this scenario as a basis, the research is mainly grounded in the ideas presented by Bauman (2011), Bourdieu and Passeron (1975), Castells (1999), Hobsbawm (1995) in order to understand how contemporary is reacting to changing historical events in what has been called the information society. On this scenario, the plot of the discussion of this work and we had painted-Arendt (1964) as a guide to the concept of crisis in teaching authority and the education crisis. Durkheim (1978) and Furlani (1990) complemented the vision of Arendt???s authority (1964), with convergent and divergent points on the subject. N??voa (1995), Alarc??o (2001), Zabala (1998), Zabalza (2004) and Postic (1990) helped on the reflection about the concerns and the new roles of the teacher. Phenomenology was used as conducting scientific method to the procedures for generation and data analysis. The research is characterized as exploratory regarding the objective and field and as empirical research on the means. From the qualitative approach semi-strutucture interview and systematic observation as techniques for data generation were used, while the collective subject discourse (DSC) and interparticipant analysis were employed as instruments for its contextualization. As a result, three important phenomena have been identified and appear to be essential to this debate: a) the student has facility to interact with technology, but this feature does not extend to their use in the context of communication and entertainment; b) Students??? access to new information bases can generate a sense of loss of authority on a teacher who might not be prepared to deal with that reality; and c) that the strategies in which are based on the understanding of the other as part directly involved in the educational act seem to strengthen the teacher???s authority relations. In summary, the result points to the idea that it is not the domain of ICT by the teacher reinforcing or not your authority.